2020
DOI: 10.3390/ijms21249580
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Short-Chain Fatty Acids in the Interplay between a Very Low-Calorie Ketogenic Diet and the Infant Gut Microbiota and Its Therapeutic Implications for Reducing Asthma

Abstract: Gut microbiota is well known as playing a critical role in inflammation and asthma development. The very low-calorie ketogenic diet (VLCKD) is suggested to affect gut microbiota; however, the effects of VLCKD during pregnancy and lactation on the infant gut microbiota are unclear. The VLCKD appears to be more effective than caloric/energy restriction diets for the treatment of several diseases, such as obesity and diabetes. However, whether adherence to VLCKD affects the infant gut microbiota and the protectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 167 publications
0
43
0
Order By: Relevance
“…In this review, we explain the hypothesized mechanism of action of KD. The literature also supports a potential role in chronic inflammatory diseases in children [ 10 ] and in adolescents who are eligible for bariatric surgery and are affected by PCOS, this treatment is currently proposed. However, clinical studies are needed to evaluate KD as a promising therapeutic tool for the treatment of metabolic and cardiovascular risk factors also in pediatrics.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In this review, we explain the hypothesized mechanism of action of KD. The literature also supports a potential role in chronic inflammatory diseases in children [ 10 ] and in adolescents who are eligible for bariatric surgery and are affected by PCOS, this treatment is currently proposed. However, clinical studies are needed to evaluate KD as a promising therapeutic tool for the treatment of metabolic and cardiovascular risk factors also in pediatrics.…”
Section: Discussionmentioning
confidence: 95%
“…SCFA, namely, butyrate, acetate, and propionate, are gut metabolic end-products that exert multiple beneficial effects on human metabolism, particularly in obese individuals [ 176 , 177 ]. Recently, studies [ 10 ] have shown changes in the gut microbiota, after adopting the ketogenic diet, suggesting a possible role of ketone bodies in altering the intestinal microbiome. Interestingly, recent preclinical data underline the possible pathogenetic role of the gut microbiome on the benefits of the KD [ 178 ].…”
Section: Ketogenic Diet: Indications In Infants and Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheng and coworkers fed mice an HFD low in carbohydrates (ketogenic), leading to an upregulation of the 3-hydroxy-3-methylglutaryl-CoA synthase 2 (HMGCS2) protein expression [ 123 ]. HMGCS2 is expressed in small intestinal Lgr5+ stem cells and produces ketone bodies, providing energy during fasting [ 124 ]. β-hydroxybutyrate, a ketone body produced by HMGCS2, facilitates Notch signaling as a signaling-active metabolite, thereby increasing the intestinal stem cell number andfunction, and promoting intestinal injury repair after radiation damage [ 124 ].…”
Section: Nutrition Microbiota and Innate Immune Signaling Adapts Gut Morphology And Cell Homeostasismentioning
confidence: 99%
“…HMGCS2 is expressed in small intestinal Lgr5+ stem cells and produces ketone bodies, providing energy during fasting [ 124 ]. β-hydroxybutyrate, a ketone body produced by HMGCS2, facilitates Notch signaling as a signaling-active metabolite, thereby increasing the intestinal stem cell number andfunction, and promoting intestinal injury repair after radiation damage [ 124 ]. Ketogenic diets (diets with low carbohydrate content, 5–10 % of total caloric intake) also impact the composition of the gut microbiota, decreasing total diversity and altering the abundance of several bacterial species [ 125 , 126 ].…”
Section: Nutrition Microbiota and Innate Immune Signaling Adapts Gut Morphology And Cell Homeostasismentioning
confidence: 99%